Sorção, dessorção e lixiviação do sulfentrazone em solos da região canavieira do nordeste Brasileiro - Braga, Daniely Formiga (2014)
Knowledge of the factors related to the dynamics of herbicides in the environment is of fundamental importance to predict the behavior of herbicides in different soil types and selection of appropriate doses and to avoid harmful effects to the environment and subsequent crops. Three experiments were conducted in order to analyze the dynamics of sulfentrazone in five soils of sugarcane areas of the Brazilian Northeast: Quartzipsamment (Peter Old-RN), Cambisol (Quixeré-CE); Oxisol (Coastal Plains - Maceió-AL), Red-Yellow Ultisol (Coastal Plains - Maceió-AL) and an Epiaquic Haplustult (floodplain - Maceió-AL). The first experiment aimed to characterize chemically, physically and mineralogically the topsoil of different soil classes. The characterization of soil attributes allowed to observe that areas with cane sugar cultivation vary depending mainly physical attributes, with soils of different textural classes and chemical attributes, highlighted with total Organic Carbon content and P available. Regarding the mineralogy, it was observed that the sugarcane areas are installed from young soils with predominance of 2: 1 clay soils to more developed with the presence of kaolinite, gibbsite and iron oxides. The second experiment aimed to evaluate the sorption and desorption of sulfentrazone in the five soils mentioned above was conducted in laboratory conditions. Freundlich equation was adjusted to obtain the sorption coefficients, Kf (sorption capacity) and 1 / n (intensity sorption). It was observed that the soils have different behavior in relation to sulfentrazone sorption potential. Based on the results of this second study, we concluded that the increasing order of sorption was: Argisol (Kf = 8.74)> Oxisol (Kf = 8.23)> Quartzipsamment (Kf = 7.50)> Inceptisol (Kf = 6 98)> Gleysol (Kf = 6.67); while desorption decreased in the following order: Argisol <Gleysol <Quartzipsamment <Inceptisol <Oxisol. The third study aimed to evaluate the leaching of sulfentrazone in these soils through bioassay and liquid chromatography high resolution. Based on the results, it is concluded that the mobility of sulfentrazone in the soil is influenced by its chemical, physical and mineralogical, presenting the following leaching potential sequence: Quartzipsamment (45 cm)> Oxisol (35 cm)> Argisol (20 cm) = Inceptisol (20 cm) = Gleysol (20 cm). Before making the recommendation of sulfentrazone, we must know the chemical, physical and mineralogical characteristics of soils and their interactions with the herbicide, in order to ensure technical efficiency and environmental sustainability